Addressing the Moral Crisis Among Generation Z: Islamic Religious Education Teachers’ Responses in the Era of Social Connectivity - Amma Ainun; Ruslan Ruslan; Kaharuddin Kaharuddin; Ikhsan Maulana; Hermansyah Hermansyah; Agus Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2025)
The rapid expansion of social connectivity and digital media has reshaped adolescents’ moral environments, posing new challenges for moral and religious education. Generation Z students, as digital natives, increasingly negotiate moral values through online interactions that may conflict with religious and educational norms. This study examines how social connectivity influences the moral challenges faced by Generation Z students and explores the responses of Islamic Religious Education (PAI) teachers within a culturally Islamic context. This study employed a qualitative descriptive design conducted in junior and senior high schools in Bima City, Indonesia. Data were collected through semi-structured interviews with 15 PAI teachers and 20 students, classroom observations, and document analysis. The data were analyzed using thematic analysis following Braun and Clarke’s framework to identify recurring patterns related to moral behavior, digital engagement, and teacher responses. The findings reveal that intensive social media use contributes to technology dependency, weakened moral reflection, declining respect for authority, and reduced engagement in religious activities. Moral decision-making among students is often shaped by peer validation and online visibility. In response, PAI teachers adopt adaptive pedagogical strategies, including integrating digital ethics into religious instruction, reinforcing discipline, and collaborating with parents and counseling services. The study highlights teacher agency as a critical mediator between digital culture and moral development, suggesting that religious education remains relevant when responsive to students’ socio-digital realities.